The Role of Semiotics Analysis In Advertisement: Bibliometric Analysis - Teguh Iman Prasetya (Journal La Sociale, 2025)
Semiotic analysis in advertising plays an important role in understanding how signs, symbols and meanings are constructed and received by audiences. With the development of digital technology and social media, an understanding of semiotics is increasingly relevant to examine how brands build identity and create emotional resonance with consumers. This research aims to analyze the development of semiotic studies in advertising using bibliometric methods with VOSviewer. With this approach, scholarly publication patterns can be mapped to identify trends, academic collaborations, as well as key topics in advertising semiotics studies. The method used in this research is a systematic literature review (SLR) combined with PRISMA-based bibliometric analysis. Data were collected from journal articles published between 2014 and 2024, then analyzed using VOSviewer software to map the linkages between concepts. The results show that the study of semiotics in advertising has experienced significant developments in the past decade, with a focus on visual and linguistic representations, mythology in advertising, and multimodality in digital media. Bibliometric network visualization reveals a close correlation between semiotic theory and strategic marketing concepts.